Answer:
Then the solution is (4, 6).
Step-by-step explanation:
Let's use the substitution method:
First multiply the second equation by 4, obtaining 4y = -2x + 32.
Now substitute (-2x + 32) for 4y in the first equation:
3x + (-2x + 32) = 36, or
3x - 2x + 32 = 36. or
x = 4.
If x = 4, then the second equation yields y = (-1/2)(4) + 8, or
y = -2 + 8, or y = 6
Then the solution is (4, 6).
Check, using the first equation:
Does 3(4) + 4(6) = 36? Does 12 + 24 = 36? YES
Answer
17.27 hours
Step-by-step explanation:
lemme know if it's good :)
Answer:
Wait is this melody Montejano from tustin high ?
Answer:
You would use the distributive property.
Step-by-step explanation:
2(x+4) = 2x+8
2x+8x = 2x+8
10x = 2x+8
10x - 2x = 2x-2x+8
8x = 8
8x/8 = 8/8
x = 1